Written Feedback in English Foreign Language Writing Instruction: A Study of Teacher Feedback in 8th and 10th Grades of the Primary School in Iceland - Steinlaug Sigríður Bjarnadóttir 1953- (2008)
This study examines the nature of written feedback in English writing in 8th and 10th grades of the compulsory school in Iceland. It investigates the amount of feedback provided and which aspects of the writing the teachers address in their feedback. It also studies the teachers´views on their teaching of writing in English and their feedback practices. The data consists of two hundred and sixty-four copies of English writing samples from students in the 8th and 10th grades collected from the teachers, 162 copies from 10th grade and 102 copies from 8th grade. Additionally, the teachers were given two questionnaires in which they were asked to respond to their English instruction and feedback practices. The feedback on the writing samples gathered was categorized according to types of feedback and types of written comments and the types were counted. The study does not reveal any significant difference between these two grades regarding the amount of feedback provided or issues addressed. The emphasis is on error correction in both grades. Only two teachers, one in each grade use written comments on content and structure. The main difference in the feedback practices is between the individual teachers. The questionnaire reveals that the teachers who use error correction report that they discuss the writing with their students when handing back the assignments. Two teachers explain they prefer oral response to written commentary.